The Relationship Between Ki-67 Expression and Post-Surgical Breast Cancer Recurrence Rates: A Systematic Review - Fiya Natilda; Miya Elmira; Desty Triyanti (International Medical Journal Corp. Ltd, 2025)
Introduction: Post-surgical recurrence remains the primary driver of mortality in breast cancer. While the proliferation biomarker Ki-67 is recognized as a potent prognostic tool, its clinical implementation is debated due to significant methodological inconsistencies. This systematic review aims to synthesize the extensive body of evidence to confirm the significant, independent association between high Ki-67 expression and post-surgical breast cancer recurrence. Methods: This review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A systematic search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library was performed for studies from January 2007 to October 2024. The PICO (Population, Intervention, Comparator, Outcome) framework was used to select high-quality cohort studies and meta-analyses. Methodological quality was assessed using the Newcastle-Ottawa Scale (NOS) for prognostic studies. Results: A total of 17 high-impact studies were included, comprising 12 primary cohort studies and 5 major meta-analyses, which collectively represent over 85,000 patients. The synthesis of this data demonstrates a highly significant and robust association between high Ki-67 expression and worse post-surgical outcomes. Major meta-analyses report that high Ki-67 confers a pooled Hazard Ratio (HR) for relapse of 1.93 (95% CI: 1.74–2.14, p < 0.001) and a pooled HR for mortality of 2.05 (95% CI: 1.66–2.53, p < 0.00001). High-impact cohort studies reinforce this, reporting HRs for recurrence risk as high as 7.14, 12.90, and even 30.47 in specific patient groups. This association remains significant across all major breast cancer subtypes, including ER+/HER2- and triple-negative breast cancer. Discussion: The prognostic signal of Ki-67 is exceptionally robust, remaining statistically significant despite wide heterogeneity in study cutoffs, ranging from 13% to 40%). This confirms its fundamental biological importance. Ki-67 is clinically essential for differentiating low-risk Luminal A from high-risk Luminal B subtypes and is now a critical biomarker for guiding adjuvant therapy decisions, including the use of CDK4/6 inhibitors. Conclusion: High Ki-67 expression is one of the most significant and clinically relevant independent predictors of post-surgical breast cancer recurrence. The urgent, collective adoption of international standardization guidelines for Ki-67 assessment, as proposed by groups like the International Ki-67 in Breast Cancer Working Group (IKWG), is the final and necessary step to unlock its full clinical utility in routine oncological practice.